Ділова французька мова: практика перекладу - Дробязко, Олена Євгеніївна; Сатановська, Ганна Сергіївна; Бєлявська, Марія Юріївна; Drobiazko, Olena; Satanovska, Hanna; Bieliavska, Mariia (Харків : Харківський національний університет імені В. Н. Каразіна, 2024)
Сучасний розвиток міжнародних ділових зв’язків, розширення сфери діяльності міждержавних організацій, зокрема на території України, викликає необхідність у підготовці фахівців-перекладачів, які мають добре орієнтуватись у діловій термінології, мати відповідний лексичний запас і забезпечувати усне і письмове спілкування сторін. Навчальні матеріали призначені для викладання у рамках вузівського курсу практики перекладу та спрямовані на поглиблення й вдосконалення вже отриманих знань під час навчання на попередніх курсах. Вашій увазі надається друга редакція цього посібника (перше видання опубліковано 1999 р.). Було оновлено основні тексти та завдання для перекладу. Матеріали складаються з чотирнадцяти уроків. Теми складаються з базових текстів, які знайомлять читача з особливостями устрою та роботи сучасних ділових організацій (банків, бірж, підприємств тощо), з відтворенням типових ситуацій в діловій галузі, а також функціонуванням фіскальних та офіційних бізнес закладів. Тематичні тексти супроводжуються низкою вправ, спрямованих на закріплення нової лексики та термінів. Посібник також має за мету розвинути практичні навички і вміння двостороннього усного і письмового перекладу у діловій галузi та забезпечити з асвоєння студентами фахової термінології, її значень і сфер вживання. Посібник розрахований на подальше вдосконалення навичок письмового та усного перекладу у межах курсу практики перекладу у сучасній бізнес сфері. Посібник призначений для студентів 3–4 курсів бакалавра та 1–2 курсів магістратури факультетів іноземних мов.

The modern development of international business relations, the expansion of the sphere of activities of interstate organizations, in particular on the territory of Ukraine, calls for the training of translation specialists who must be well versed in business terminology, have an appropriate vocabulary and ensure oral and written communication between the parties. The educational materials are intended for teaching as part of a university translation practice course and are aimed at deepening and improving the knowledge already acquired during training in previous courses. Your attention is drawn to the second edition of this manual (the first edition was published in 1999). Main texts and tasks for translation have been updated. The materials consist of fourteen lessons. The topics consist of basic texts that acquaint the reader with the peculiarities of the structure and work of modern business organizations (banks, stock exchanges, enterprises, etc.), with the reproduction of typical situations in the business industry, as well as the functioning of fiscal and official business institutions. Thematic texts are accompanied by a number of exercises aimed at consolidating new vocabulary and terms. Each lesson ends with two types of translation of phrases with typical vocabulary and terminology - from French into Ukrainian and from Ukrainian into French, which aims to consolidate the learned vocabulary and terminology in practice. The manual also aims to develop practical skills and abilities of two-way oral and written translation in the business field and to ensure that students learn professional terminology, its meanings and areas of use. The manual is also designed for further improvement of written and oral translation skills within the scope of the translation practice course. The materials as a whole are aimed at improving translation skills in the modern business sphere. The manual is intended for students of the 3rd-4th year of the bachelor's degree and the 1st-2nd year of the master's degree of foreign language faculties.
Business french language: translation practice
Keywords: banque; secrétariat; sociétés françaises; service des achats; service des ventes; банк; секретаріат; французькі компанії; Торгово-промислова палата і промисловість; Chambre de commerce et d’industrie; Chamber of Commerce and Industry; French Companies; HUMANITIES and RELIGION::Languages and linguistics